Severe acute malnutrition in Asia - Ahmed, Tahmeed; Hossain, Muttaquina; Mahfuz, Mustafa; Choudhury, Nuzhat; Hossain, Mir Mobarak; Bhandari, Nita; Lin, Maung Maung; Joshi, Prakash Chandra; Angdembe, Mirak Raj; Wickramasinghe, V. Pujitha; Hossain, S. M. Moazzem; Shahjahan, Mohammad; et al. (© 2014 United Nations University Press, 2017)
This article was published in Food and Nutrition Bulletin [© 2014 United Nations University Press] and the definite version is available at: http://journals.sagepub.com/doi/abs/10.1177/15648265140352S103